Dermoscopy of shagreen patch: A first report - Shivanand Gundalli; Balachandra S Ankad; Ashwin PK; Rutuja Kolekar (Our Dermatology Online, 2015)
The name is derived from French phrase peau chagrinee which is usually found on lower back, buttock and thigh. The major manifestations of Tuberous sclerosis include skin lesions in more than 95%, mental retardation in approximately 50%, autism, seizures in approximately 85%. The incidence at birth is estimated to be 1 in 5800. We report case of shagreen patch in a 27 year female which is present since birth. However there is no history of seizures or consanginous marriage in our case. Associated features are naevus comedonicus and naevus collagenosis, facial angiofibroma. Shagreen patch are present in mandibular area of face. Although, diagnosis is easy, it can be mistaken for inflammatory verrucous epidermal nevus, plaques of other inflammatory skin conditions. Diagnosis is usually on clinical background. Sometimes biopsy is necessary to confirm the diagnosis. Dermoscopy, a non-invasive, in vivo technique for the microscopic examination of pigmented skin lesions, has the potential to improve the diagnostic accuracy. Dermoscopy of Shagreen patch showed reddish-brown strands with white dots giving a cobblestone appearance It can be utilized as a diagnostic aide in the diagnosis of Shagreen patch. Authors evaluated the dermoscopic patterns of Shagreen patch and hence, it is useful in diagnosis.